Magnetic Resonance Imaging-Guided Adaptive Brachytherapy for the Treatment of Cervical Cancer and its Impact on Clinical Outcome. Issue 7 (July 2022) - Singhal, S.; Veeratterapillay, J.; Locks, S.; Morgan, D.; Patil, R.; Chamberlain, H.M.
Abstract: Aims: We implemented magnetic resonance imaging-based image-guided adaptive brachytherapy (IGABT) for the management of cervical cancer at the Northern Centre for Cancer Care in January 2015. The Royal College of Radiologists recommended IGABT as the new standard of care for the management of cervical cancer in the UK in 2009, following earlier publication of recommendations of Groupe European de Curietherapie of the European Society for Radiotherapy and Oncology for three-dimensional magnetic resonance imaging-based IGABT. The purpose of this study was to investigate if the introduction of IGABT in the management of cervical cancer at our institute indeed improved the treatment outcomes with a better toxicity profile as compared with conventional brachytherapy (CBT). Patients and methods: A retrospective analysis of 213 patients with International Federation of Gynecology and Obstetrics stage IB–IVA cervical cancer treated with curative radiotherapy ± chemotherapy at the Northern Centre for Cancer Care was carried out for the period January 2010 to December 2019. Patients were categorised into three groups based on their brachytherapy planning process. Fifty-eight patients were treated with CBT, 35 patients were treated with retrospective brachytherapy (RBT) planning and 120 patients were treated with IGABT. Eighty-six per cent received concomitant chemotherapy with cisplatin. Outcome measures were local control rates, overall and progression-free survival, and impact on treatment-related toxicities. Results: The median follow-up was 36, 32 and 25 months for CBT, RBT and IGABT, respectively. Three-year local control achieved was 70.4, 77.8 and 86.9%, respectively. Three-year overall survival was 53.8, 61.1 and 86.2%, respectively. Grade 2 or 3 bladder and bowel toxicity was 8% and 10% in IGABT group versus 20% and 27% in the CBT group. Conclusion: Our analysis indicated that IGABT proved to be very effective in not only improving locoregional control, but also offered quality survivorship to these women, with a significant drop in radiation-related bladder and bowel toxicities. Highlights: Adoption of IGABT significantly improved patient outcome, quality of treatment and reduced treatment related toxicity, as compared with CBT. Interstitial needles along with intrauterine tube/vaginal rings allowed better optimisation of the brachytherapy plan and escalation of HR CTV dose. We should be actively encouraging women to stop smoking and involving smoking cessation services in treatment pathway.